AGE ESTIMATION OF PERMANENT TEETH AND ITS CORRELATION AMONG LOCAL POPULATION - SINGH, JASPINDER PRATAP; CHAUDHARY, NEHA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The aim of this study was to establish the relationship between the ages of the eruption of permanent teeth in correlation with the local population and related factors. Methods: The present prospective observation study was conducted on one thousand students in schools and colleges aged 6–25 years by the Department of Forensic Medicine and Toxicology, Government Medical College, Amritsar. The data collected from this study were organized by presenting it in appropriate tables and graphs, which are statistically analyzed for percent ages and inferences. Results: The first permanent tooth to erupt is the first permanent Molar, which erupts at 75.9–77.9 months; permanent central incisor is the second permanent tooth to erupt following the first Molar. The age of eruption is 80.8–84.0 months. Permanent Lateral Incisor erupts at the age of 105.2– 107.4 months, and permanent Premolar one teeth erupt at the age of 109.5–112.6 months, permanent premolar two teeth erupt at the age of 131.0– 133.8 months, permanent Canine teeth erupt at the age of 142.6–144.8 months. Conclusion: It is thus concluded, based on the present study that the growth and eruption of teeth depend on various factors, including genetic as well as ecological aspects. The most accurate method, which depends on the conditions as well circumstances of each case, namely, the elements can be age, people participating in the study, supporting networks, availability of tools of age estimation, culture, religion, and ethnicity of the individual.